MANAGEMENT STANDARDIZATION FOR SUSTAINED SUCCESS AS A COMPULSORY DISCIPLINE IN TRAINING SPECIALISTS - Yu. S. Klochkov; A. D. Shadrin (Moscow Polytechnic University, 2017)
A specialist of any profession should acquire knowledge, skills and abilities in three areas in the process of training. The first area concerns the ensuring of the quality of relevant products (or services). Achieving this goal is the essence of a particular specialty. The second area is ensuring of effective management of organization, which produces these products (services). The third is ensuring of the requirements of all stakeholders including society. Joint achievement of the last two goals of the study may be promoted by the use of the principles and obtaining skills and techniques regulated by modern management standards.